2013
DOI: 10.1123/ijatt.18.5.22
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy Effects, Part 1: Comparison of Skin Temperatures and Patient-Reported Sensations for Different Modes of Administration

Abstract: ryotherapy is commonly administered to relieve musculoskeletal pain for both acute and chronic injuries. 1 Although cold application is often used for inflammation, recent research evidence suggests that the primary benefit of cryotherapy treatment may be decreased pain that results from changes in skin sensation. 2 The beneficial effects of cold on joint function also appear to relate to a sensory effect. 3 Cryotherapy alters cutaneous sensory input to the central nervous system through various mechanisms, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
1
6
0
4
Order By: Relevance
“…From time 1 to time 2, the mean decreases in temperature were 7.258C over the ATFL was and 6.878C over the deltoid ligament. This finding is consistent with the results of other research [46][47][48] showing that skin temperature decreased with cryotherapy application. Whereas different, our temperature decreases were small when compared with those from other cryotherapy modalities: Love et al 46 observed decreases of 188C, 26.48C, and 19.58C using an ice bag, ice massage, and cold-water immersion, respectively.…”
Section: Skin Temperature Changessupporting
confidence: 96%
“…From time 1 to time 2, the mean decreases in temperature were 7.258C over the ATFL was and 6.878C over the deltoid ligament. This finding is consistent with the results of other research [46][47][48] showing that skin temperature decreased with cryotherapy application. Whereas different, our temperature decreases were small when compared with those from other cryotherapy modalities: Love et al 46 observed decreases of 188C, 26.48C, and 19.58C using an ice bag, ice massage, and cold-water immersion, respectively.…”
Section: Skin Temperature Changessupporting
confidence: 96%
“…Por sua vez, o estímulo dos receptores de frio e das fibras sensitivas gera uma série de sensações cutâneas, que são, geralmente, descritas em termos de frio, formigamento, queimação, dor e adormecimento. Estas sensações ocorrem de modo progressivo e dependem do grau de estimulação das fibras sensitivas, ou seja, quanto maior for a velocidade do arrefecimento mais rapidamente elas ocorrerão (Knight, 2000;Starkey, 2001;Prentice, 2002;Guyton, Hall, 2006;Galvan et al, 2006;Love, Pritchard, Hart, 2013). Entretanto, essas sensações poderão ser minimizadas, se as informações sobre a percepção sensorial, que ocorrerá durante o arrefecimento, forem fornecidas previamente ao indivíduo em tratamento (Streator, Ingersoll, Knight, 1995).…”
Section: Sistema Nervoso Periféricounclassified
“…Mas, as multíparas descreveram maior variedade de sensações, como frio e gelado, queimação, formigamento, incômodo, alívio e dormência local (Paiva, 2014). Achados semelhantes aos do atual estudo também foram relatados em pesquisas na área de fisiologia humana que investigaram os efeitos da aplicação de diversas modalidades de crioterapia em diferentes áreas do corpo (Davis, 1998;Love, Pritchard, Hart, 2013;Cataldi, Pritchard, Saliba, 2013). Assim, considerando que esta variável foi obtida por meio de uma questão aberta em nosso questionário "O que você sentiu durante a aplicação da bolsa de gelo?…”
Section: 5sensações E Satisfação Das Puérperasunclassified
See 1 more Smart Citation
“…Durante a imersão em água fria, os participantes relataram a sensação de frio durante os primeiros 3 minutos, sensação alterada entre 4-5 minutos, e dormência com 6 minutos. Durante o tratamento com saco de gelo triturado, os participantes relataram frio nos primeiros 2 minutos, sensação alterada durante 3-9 minutos, e dormência em 10 minutos de aplicação (Cataldi et al, 2013;Love et al, 2013).…”
Section: Aspectos éTicosunclassified